Perceptions of role ambiguity for Sporting Directors in professional football - Parnell, D.; Easton, B.; Bond, A.; Kelly, S. (Soccer & Society, 2022)
The Sporting Director is one strategy football clubs have adopted to protect their financial sustainability. Little to no research has been undertaken on the Sporting Director role in football. This article draws upon a qualitative methodology to examine perceptions and practices related to the role and its potential implications in football`s growing global business. Semi-structured interviews were undertaken with senior stakeholders in football (N = 21). The data was thematically analysed. Findings indicate that the Sporting Director role would be a strategic benefit for football clubs, however several issues related to role ambiguity. The novel empirical insight surrounds three key themes, notably the perception of the role, job description clarity and communication. The study provides novel insights into the elite football stakeholder perceptions of the Sporting Directors. This research offers decision-makers considerations for developing the Sporting Director role in football and recommendations for future research.